Polycystic Ovary Syndrome (PCOS) Is Associated With NASH Severity and Advanced Fibrosis - Sarkar, Monika (Liver Int, 2019)
BACKGROUND: Polycystic ovary syndrome (PCOS) affects 10% of reproductive-aged women, and is marked by irregular menses and high androgens. PCOS is a known risk factor for imaging-confirmed steatosis, and we now aim to evaluate whether PCOS influences histologic severity of non-alcoholic fatty liver disease (NAFLD). METHODS: Retrospective study of women ages 18–45 years with biopsy-confirmed NAFLD between 2008–2019. Metabolic co-morbidities were captured within 6 months of biopsy. Histologic features of non-alcoholic steatohepatitis (NASH) were independently evaluated by two pathologists blinded to PCOS status. RESULTS: Among 102 women meeting study criteria, 36% (n=37) had PCOS; median age was 35 years; 27% were white, 6% black, 19% Asian, and 47% reported Hispanic ethnicity. Women with PCOS had higher LDL (123 vs 101 mg/dL, p=0.02) and BMI (38 vs 33 kg/cm(2), p<0.01). NASH was present in 76% of women with PCOS vs 66% without PCOS (p=0.3), and a higher proportion with PCOS had severe ballooning (32 vs 13%, p=0.02), presence of any fibrosis (84 vs 66%, p=0.06), and advanced fibrosis (16 vs 6%, p=0.10). Adjusted for age and BMI, PCOS remained associated with severe hepatocyte ballooning (OR 3.4, 95% CI 1.1–10.6, p=0.03) and advanced fibrosis (OR 7.1, 95% CI 1.3–39, p=0.02). Among women with advanced fibrosis, median age was 5 years younger in those with as compared to those without PCOS (40 vs 45 years, p=0.02). CONCLUSION: PCOS is independently associated with more severe NASH, including advanced fibrosis. Hepatologists should routinely inquire about PCOS in reproductive-aged women with NAFLD, and also evaluate for more severe liver disease in this population.